Agricultural intensification, dietary diversity, and markets in the global food security narrative - Ickowitz, A.; Powell, B.; Rowland, D.; Jones, A.; Sunderland, T.C.H. (Elsevier, 2019)
• Many food security experts have been calling for agricultural intensification in developing countries to feed a growing global population. • This narrative is based on a narrow view of food security focused on calories and neglects issues of dietary quality. • Encouraging small farmers across the developing world to grow more staple crops more intensively may have unintended negative consequences on dietary quality. • A more nuanced approach sensitive to local contexts and appreciative of foods other than staples may lead to alternative policy choices in many places.